Evolution of Global Value Chains Participation and Economic Growth in Africa - Ibrahim Nana; Martin Paul Tabe-Ojong (Research Network Sustainable Global Supply Chains, 2023)
Global value chains offer countries unique opportunities to participate in and benefit from international trade by specializing in specific production stages and tasks. The objective of this study is twofold: (i) to investigate the evolution of African countries participation in global value chains and (ii) assess the impact of global value chains participation on growth. We use the EORA Multi-Region Input-Output tables to track the evolution of African countries along global value chains, identify specialization patterns, and generate sector/task global value chains participation measures. Further, using panel data from 48 African countries over the period 1990-2016, we employ both the instrumental variable approach and the local projection method to investigate the relationship between global value chains participation and growth, and provide evidence on the sectors that drive the relationship. The findings suggest that African countries' participation in global value chains positively impacts their growth; a positive impact which is driven by trade in commodities, knowledge intensive good and regional processing. We discuss some key policy implications, including the necessity to promote skill upgrading, skill-based technological change, and various education and labor market programs.
Keywords: F14; F15; F43; O47; O55; 330; Global Value Chains; Trade; Growth; Africa